Effect of reactive time on flame retardancy and thermal degradation behavior of bio-based zinc alginate film. (May 2016) - Liu, Yun; Zhao, Xi-Ran; Peng, Ya-Li; Wang, Dan; Yang, Lingwei; Peng, Hao; Zhu, Ping; Wang, De-Yi
Abstract: A bio-based zinc alginate film was prepared via a facile ionic exchange and casting approach. Effects of reactive time on the flame retardancy and thermal stabilities of zinc alginate film were studied systemically; and the pyrolysis mechanism of zinc alginate was investigated. According to the results in vertical burning (UL-94) and thermogravimetric analysis (TGA) tests, the optimized reactive time was 2 h. Microscale combustion calorimetry (MCC) results indicated that the addition of zinc ion significantly increased the flame retardancy of alginate, showing in the reduction of peak heat release rate (PHRR), from 105 to 12.0 W/g; and the reactive time had no obvious effect on the reduction of PHRR for zinc alginate. Thermogravimetric analysis coupled with Fourier transform infrared analysis (TG-FTIR) and pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) results showed that zinc alginate produced much less flammable products than sodium alginate did in whole thermal degradation process. The results implied that zinc ion had the catalysis effect during the pyrolysis process. Finally, the possible thermal degradation mechanism of zinc alginate was proposed.